Heteromorphism for Heterokaryon Incompatibility Genes in Natural Populations of NEUROSPORA CRASSA - Mylyk, Orest M. (1976)
Five Neurospora crassa isolates from each of three sites in Louisiana were compared for genotype at five heterokaryon incompatibility (het) loci. The comparisons were made using duplications (partial diploids), based on the fact that duplications heterozygous for het loci have strikingly abnormal phenotypes which greatly facilitate the study of such genes. Duplications were synthesized in crosses between the wild strains (normal chromosome sequence) and testers of defined het genotype and having duplication-producing chromosome rearrangements. Crosses segregating for phenotypes characteristic of duplications heterozygous for het loci indicated allelic differences between testers and wild strains for specific het genes. Whenever a wild strain differed from a tester for a specific het locus, but another wild strain did not, the two wild strains could be inferred to differ from each other.—No two isolates from any site were heterokaryon compatible (of identical het genotype), despite the fact that all isolates from each of two sites occurred within several meters of each other. Heteromorphism was found for all five genes studied at one site, four genes at another site, and three at another. Intra- and interpopulation differences between strains were approximately the same.—Confirmation is also provided that two het genes originally detected in duplications are in fact heterokaryon incompatibility loci.